A rare cause of progressive gait abnormality in a case of Turner syndrome - Patil, Ajinkya; Jahagirdar, Rahul; Srivastava, Kavita; Mankar, Sanjay (International Journal of Contemporary Pediatrics, 2021)
Turner syndrome is a commonly encountered chromosomal disorder affecting females, while Duchenne muscular dystrophy is a severe X-linked recessive disorder affecting males. Although theoretically possible, very few cases of DMD associated with Turner syndrome have been reported. We report an 8 year old girl who presented with a rare association of Turner syndrome mosaicism (45X/46XringX) with Duchenne muscular dystrophy.